1997
DOI: 10.1177/002204269702700309
|View full text |Cite
|
Sign up to set email alerts
|

Women and Children in Residential Treatment: Outcomes for Mothers and Their Infants

Abstract: This paper examines the relationship between the living arrangement of mother and baby in a residential treatment center and measures of self-esteem, depression and parenting sense of competence and a woman's length of stay and completion or non-completion of treatment. Scores on the Bayley Scales of Infant Development (Bayley 1969) are also examined by the amount of time the baby spent with mother, an arrangement that affords the opportunity for the child to participate in the facility's therapeutic child car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…There is initial evidence to suggest that incorporating family components in transitional programing can positively enhance outcomes. For example, researchers have documented that women who are allowed to live with their children while completing residential treatment are more likely to complete the program (Utziel-Miller, Lyons, Kissiel, & Love, 1998;Wobie, Eyler, Conlon, Clarke, & Behnke, 1997). Correctional officials should continue to be cognizant of the legal challenges facing many women in maintaining parental rights, and be flexible to women's specific needs of managing family responsibility with other obligations (Berman, 2005;Pollock, 2002a).…”
Section: Discussionmentioning
confidence: 99%
“…There is initial evidence to suggest that incorporating family components in transitional programing can positively enhance outcomes. For example, researchers have documented that women who are allowed to live with their children while completing residential treatment are more likely to complete the program (Utziel-Miller, Lyons, Kissiel, & Love, 1998;Wobie, Eyler, Conlon, Clarke, & Behnke, 1997). Correctional officials should continue to be cognizant of the legal challenges facing many women in maintaining parental rights, and be flexible to women's specific needs of managing family responsibility with other obligations (Berman, 2005;Pollock, 2002a).…”
Section: Discussionmentioning
confidence: 99%
“…Four quantitative studies-the randomized two-group design studies of Hughes et al (1995) and Stevens and Patton (1998), the nonrandomized three-group design study of Metsch et al (2001), and the nonrandomized two-group design study of Wobbie et al (1997)-found that the mothers whose child stayed with them during residential treatment had a significantly longer LOS or were more likely to complete the treatment than the mothers whose child was not with them during treatment.…”
Section: Provision For Child Carementioning
confidence: 99%
“…Lack of personal efficacy, concerns over the burden of administrative procedures, and mistrust of service providers, have all been found to lead to lower utilization rates (Richman and Stagner, 1986). Preg-nancy or child care responsibility can affect utilization of substance and mental health services because women may not seek treatment for fear of losing custody of their children or because arranging child care is difficult (Bass and Jackson, 1997;Comfort, Loverro, and Kaltenbach, 2000;Howell and Chasnoff, 1999;Nelson-Zlupko, Kauffman, and Dore, 1995;Wobie et al, 1997). Finally, costs associated with treatment and lack of insurance coverage may also reduce mental health service utilization rates (Derr, Hill, and Pavetti, 2000;Melfi, Croghan, and Hanna, 1999;SAMHSA, 1999).…”
Section: Social Service Utilization Among Welfare Mothersmentioning
confidence: 99%